UPAYA PENINGKATAN KEMAMPUAN TEKNIK DASAR PASSING DAN STOPPING DALAM PERMAINAN SEPAKBOLA MELALUI METODE VARIASI LATIHAN SISWA KELAS V SDN 003 BATU BERSURAT KABUPATEN KAMPAR - Nurdiati Nurdiati (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This research is motivated by the low ability of basic technique of passing and stopping students of grade V SDN003 Batu Bersurat, Kampar. This study aims to determine the basic engineering capabilities of passing andstopping on the subjects of PJOK through the method of variation of exercise Class V student SDN 003 BatuBersurat, Kampar. The subjects of this study were Class V SDN 003 Batu Bersurat, Kampar with the number ofstudents as many as 22 people. The form of research is classroom action research. The instrument of thisresearch consisted of performance instrument and data collection instrument in the form of observation sheet ofteacher activity and student activity. Based on the results of the analysis and discussion it can be concluded thatthrough the method of exercise variation can improve the basic engineering skills of passing and stopping onstudents V SDN 003 Batu Bersurat, Kampar.